2015
DOI: 10.1007/s00405-015-3864-6
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy: what is it and what is its awareness?

Abstract: In expanding the scope of sialendoscopy across the globe and assessing the impact of training activities at the European Sialendoscopy Training Centre, this study was conducted to find out the knowledge and attitude among respondents as well as identify potential obstacles to the initiation of the procedure. Delegates attending the 2011 International Federation of Otorhinolaryngological Societies meeting received a set of five questions. There were a total of 257 responses from 57 countries. Nearly all (238/25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sialendoscopy, which was introduced in Europe before 1991, is a minimally invasive diagnostic and therapeutic technique that allows access to the salivary duct system in order to look for causes that cannot be identified by means of conventional imaging techniques . The various flexible, semi‐rigid or variable ultra‐thin scopes currently available have an irrigation channel that allows the salivary duct system to be irrigated saline solution and steroids, and Antoniades et al . have shown that simple intraductal saline irrigation reduces episodes of gland inflammation regardless of the cause.…”
mentioning
confidence: 99%
“…Sialendoscopy, which was introduced in Europe before 1991, is a minimally invasive diagnostic and therapeutic technique that allows access to the salivary duct system in order to look for causes that cannot be identified by means of conventional imaging techniques . The various flexible, semi‐rigid or variable ultra‐thin scopes currently available have an irrigation channel that allows the salivary duct system to be irrigated saline solution and steroids, and Antoniades et al . have shown that simple intraductal saline irrigation reduces episodes of gland inflammation regardless of the cause.…”
mentioning
confidence: 99%